SOLAR PHOTOVOLTAIC TECHNOLOGIES AND APPLICATIONS: A CASE STUDY OF PAKISTAN - Nadir Mehran; Kifayat Ullah Khan; Muhammad Farhan (Spectrum of Engineering Sciences, 2025)
This research paper analyzes the situation of the development of solar photovoltaic (PV) technologies and their usage, paying particular attention to the outstanding absorption of solar energy in Pakistan. It has become one of the world's fastest-growing solar markets, and solar additions contributing to about a third of the national total generating capacity were completed in 2024 alone. This paper examines the different PV technologies comprising monocrystalline, polycrystalline, and thin-film solar panels, as well as their efficiency qualities and how specific technologies can be used in the wind and solar energy sector in Pakistan. The article examines the factors that are causing the solar explosion in Pakistan: they include unreliable supplies of electricity, increasing energy prices, and government policy. This paper examines some PV technologies such as monocrystalline, polycrystalline, and thin-film solar panels, their efficient nature, and their particular application in the Pakistan energy sector. The paper discusses the factors that have fueled the solar boom in Pakistan, and they include an unstable electricity supply, an increase in the cost of electricity, and favorable government regulations. This work analyzes market data, policy guidelines, and technology applications in detail to give implications of how developing countries can adopt the use of solar PV technology to improve energy security issues. The results show that the solar market in Pakistan has been increasing since 2023 when it reached 2.9 GW of imports, 16 GW in 2024, and by 2024, it is recommended that the country becomes a global leader in solar energy consumption, as the case with Pakistan. The vast majority of solar is being added on the frontier of renewable installations; Pakistan is one of the fastest-growing solar markets in the world, with solar providing a share of about a third of the entire generating capacity added in 2024 alone. By conducting a detailed study of the market trends, policymaker regulations, and technological execution, this study gives a clear idea of how the Third World countries can use solar PV technology to meet energy security issues. The conclusion shows that the solar market of Pakistan increased during the year 2024 (16 GW of imports) in comparison to 2023 (2.9 GW of imports), making the country one of the global leaders in adopting solar energy Keywords Solar photovoltaic, renewable energy, Pakistan, energy policy, solar technology, sustainable development